2022
DOI: 10.3390/rs14092220
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Method of Rainfall Field Retrieval Based on the Combination of Earth–Space Links and Horizontal Microwave Links

Abstract: High-precision retrieval of rainfall over large areas is of great importance for the research of atmospheric detection and the social life. With the rapid development of communication satellite constellations and 5G communication networks, the use of widely distributed networks of earth–space links (ESLs) and horizontal microwave links (HMLs) to retrieve rainfall over large areas has great potential for obtaining high-precision rainfall fields and complementing traditional instruments of rainfall measurement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…However, OK weights are a set of optimal coefficients based on the relationship between distance and semi‐variance (David et al., 1984). In addition, related studies have shown CML products interpolated by OK have excellent results in rainfall field reconstruction (Eshel et al., 2021; Graf et al., 2021; Haese et al., 2017; Zhao et al., 2022). The procedure of OK is as follows: Calculate the distance h ij and the semi‐variance γ ij between measurement points: hij=XiXj2+YiYj2, ${h}_{ij}=\sqrt{{\left({X}_{i}-{X}_{j}\right)}^{2}+{\left({Y}_{i}-{Y}_{j}\right)}^{2},}$ γij=12RiRj2, ${\gamma }_{ij}=\frac{1}{2}{\left({R}_{i}-{R}_{j}\right)}^{2},$ where R i is the rainfall intensity of the measurement point ( X i , Y i ) and γ ij is the semi‐variance between the i th and j th measurement points. The spherical model is adopted to fit the relationship between distance and semi‐variance to acquire the expression of the variance function γ . The semi‐variance between each measurement and the interpolated point is calculated according to γ , and the weight coefficient of measurement points can be solved by the weight matrix: []γ11γ12γ1n1γ21γ22γ2n1γn1γn2γnn11111[]λ1λ2…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, OK weights are a set of optimal coefficients based on the relationship between distance and semi‐variance (David et al., 1984). In addition, related studies have shown CML products interpolated by OK have excellent results in rainfall field reconstruction (Eshel et al., 2021; Graf et al., 2021; Haese et al., 2017; Zhao et al., 2022). The procedure of OK is as follows: Calculate the distance h ij and the semi‐variance γ ij between measurement points: hij=XiXj2+YiYj2, ${h}_{ij}=\sqrt{{\left({X}_{i}-{X}_{j}\right)}^{2}+{\left({Y}_{i}-{Y}_{j}\right)}^{2},}$ γij=12RiRj2, ${\gamma }_{ij}=\frac{1}{2}{\left({R}_{i}-{R}_{j}\right)}^{2},$ where R i is the rainfall intensity of the measurement point ( X i , Y i ) and γ ij is the semi‐variance between the i th and j th measurement points. The spherical model is adopted to fit the relationship between distance and semi‐variance to acquire the expression of the variance function γ . The semi‐variance between each measurement and the interpolated point is calculated according to γ , and the weight coefficient of measurement points can be solved by the weight matrix: []γ11γ12γ1n1γ21γ22γ2n1γn1γn2γnn11111[]λ1λ2…”
Section: Methodsmentioning
confidence: 99%
“…However, OK weights are a set of optimal coefficients based on the relationship between distance and semi-variance (David et al, 1984). In addition, related studies have shown CML products interpolated by OK have excellent results in rainfall field reconstruction (Eshel et al, 2021;Graf et al, 2021;Haese et al, 2017;Zhao et al, 2022). The procedure of OK is as follows:…”
Section: Ok Interpolation Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, with the development of satellite communications, a large number of satellites are expected to be launched in the near future [205]. Therefore, fusing opportunistic rainfall information from ESLs may be a topic for improving and expanding rainfall estimation based on CMLs [187,206,207]. However, most of the existing studies are still limited to examining rainfall measurement techniques based on CMLs and ESLs separately, and works on combining CMLs and ESLs have not yet been emphasized [208].…”
Section: Combination With Earth-space Microwave Linksmentioning
confidence: 99%